Analyzing the Ways to Improve Personnel Management in the Pharmaceutical Industry of Kazakhstan - Kairat Zhakipbekov (Journal of Global Pharma Technology, 2018)
The analysis of foreign and Kazakh literature that addressed the problem of finding ways to improve personnel management in the pharmaceutical industry showed that such factors as intensifying competition on the world market, complication of the internal and external environments of the pharmaceutical industry, and discrepancies between the actual conditions and the demands of the pharmaceutical labor market necessitated the search for new ways of improving the effectiveness of modern pharmaceutical organizations, the cornerstone in which is the human factor. Modern approaches to personnel management and trends in the improvement of personnel management in the pharmaceutical industry of Kazakhstan were analyzed; the profile of an average pharmacist was built: a woman (75.3%) aged 36-55 (52.3%), with 26-30 years of work experience (32.3%) and higher education in pharmacy (77.2%). Sociological studies discovered the following problems: the need for innovations in personnel management in the pharmaceutical industry, which should be aimed at the professional and personal development of each individual in particular and the entire pharmaceutical team in general; the need for an algorithm of consistent performance appraisal of pharmacists  and an algorithm of planning and progress of the professional career of a pharmacist; personnel departments require recommendations regarding methods for improving the organization of personnel management, with a view to continuously improving the skills of pharmaceutical personnel. A textbook for the postgraduate occupational training of pharmacists titled Communication Skills was drafted and implemented in the learning process of a higher educational institution.Keywords: Appraisal, Communication skills pharmacy, Reserve, Personnel management, Social and psychological climate.